The Victory of Hope over Angst? Funding, Asset Allocation, and Risk-Taking in German Public Sector Pension Reform - Raimond H. Maurer; Olivia S. Mitchell; Ralph Rogalla (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2007)
Public employee pension systems throughout the developed world have traditionally been of the pay-as-you-go (PAYGO) defined benefit (DB) variety, where pensioner payments are financed by taxes (contributions) levied on the working generation. But as the number of retirees rises relative to the working-age group, such systems have begun to face financial distress. This trend has been exacerbated in many countries, among them Germany, by high unemployment rates producing further deterioration of the contribution base. In the long run, public sector pension benefits will have to be cut or contributions increased, if the systems are to be maintained. An alternative path sometimes offered to ease the crunch of paying for public employee pensions is to move toward funding: here, plan assets are gradually built up, invested, and enhanced returns devoted to partly defray civil servants' pension costs. In this study, we evaluate the impact of introducing partial prefunding, paired with a strategic investment policy for the German federal state of Hesse. The analysis assesses the impact of introducing a supplementary tax-sponsored pension fund whose contributions are invested in the capital market and used to relieve the state budget from (some) pension payments. Our model determines the expectation and the Conditional Value-at-Risk of economic pension costs using a stochastic simulation process for pension plan assets. This approach simultaneously determines the optimal contribution rate and asset allocation that controls the expected economic costs of providing the promised pensions, while at the same time controlling investment risk. – – Wie in vielen anderen Ländern auch, beruhen die deutschen Beamtenpensionen traditionell auf einem umlage- und steuerfinanzierten System der Leistungszusage (defined benefit pension - DB). Aufgrund fehlender Rücklagen resultieren aus den Pensionsverspechen ungedeckte Verbindlichkeiten in Milliardenhöhe, die als solche jedoch nicht offiziell als Staatsverschuldung ausgewiesen werden. Das damit einhergehende Problem steigender Belastungen zukünftiger Haushalte wurde von der Politik erkannt, und erste Schritte in Richtung Kapitaldeckung wurden mit der Einführung der Versorgungsrücklagen sowie der Finanzierungsfonds vollzogen. Vor diesem Hintergrund evaluiert diese Studie die Chancen und Risiken, die mit dem Übergang zu einem (partiell) kapitalgedeckten Beamtenpensionssystems verbunden sind. Als Datengrundlage dient hierzu die vollständige Personalstandsstatistik des Landes Hessen, dessen Beamtenpopulation repräsentativ für den größten Teil des deutschen Beamtensystems ist. Unter Verwendung eigens für diese Studie berechneter Beamtensterbetafeln werden zunächst die Pensionsansprüche der aktuellen Pensionäre sowie die bereits erdienten Anwartschaften der aktuell diensttuenden Beamten aktuariell bewertet. Auf Grundlage einer 50-Jahres-Prognose der Beamtenpopulationsentwicklung werden die zur Finanzierung der Pensionsversprechen benötigten Beiträge, d.h. der Beitragssatz in Bezug auf die Beamtengehälter, deterministisch bestimmt. Im Rahmen einer Monte Carlo-Studie und auf Basis eines stochastischen Barwert-Ansatzes wird sodann die Anlagestrategie für das Planvermögen bestimmt, die zu minimalem Crash-Risiko, gemessen als Conditional Value at Risk der gesamten Pensionskosten, führt. Abschließend wird aufgezeigt, welchen Freiraum der Pensionsplanmanager hinsichtlich der Wahl von Beitragssatz und Anlagestrategie hat, wenn er nur auf Einhaltung eines vorgegebenen Risikobudgets verpflichtet wurde.
Keywords: 330; Ruhegehalt; Rentenreform; Kapitaldeckungsverfahren; Deutschland